2020
DOI: 10.3390/app10228252
|View full text |Cite
|
Sign up to set email alerts
|

TFBN: A Cost Effective High Performance Hierarchical Interconnection Network

Abstract: In order to fulfill the increasing demand for computation power to process a boundless data concurrently within a very short time or real-time in many areas such as IoT, AI, machine learning, smart grid, and big data analytics, we need exa-scale or zetta-scale computation in the near future. Thus, to have this level of computation, we need a massively parallel computer (MPC) system that shall consist of millions of nodes; and, for the interconnection of these massive numbers of nodes, conventional topologies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Compared to the control, the conversion rate with ginger as a component. According to the findings of [9][10][11][12][13], garlic supplementation in broiler boosted feed intake, body weight growth, the FCR, and the morphometric of the digestive tract. [14][15][16][17], found that adding red ginger as a photobiotic in broiler rations of up to 2.0 percent had a positive impact on feed intake, total body weight increase, and feed conversion.…”
Section: Resultsmentioning
confidence: 99%
“…Compared to the control, the conversion rate with ginger as a component. According to the findings of [9][10][11][12][13], garlic supplementation in broiler boosted feed intake, body weight growth, the FCR, and the morphometric of the digestive tract. [14][15][16][17], found that adding red ginger as a photobiotic in broiler rations of up to 2.0 percent had a positive impact on feed intake, total body weight increase, and feed conversion.…”
Section: Resultsmentioning
confidence: 99%
“…The proposed TFBN's static network performance was evaluated previously, and its superiority over other networks was established in our initial study on TFBN [23]. This paper investigates and analyses the density parameters called message traffic density and packing density, and the trade-off between them.…”
Section: Static Network Performance Of a Tfbnmentioning
confidence: 99%
“…The hop distance parameters were simulated using a dimension order routing algorithm. Both diameter and average distance have been enlisted in Table 1, which shows that the hop distance parameters of the proposed TFBN [23] outperforms the 2D and 3D mesh and torus networks and hierarchical TTN and TESH network for 256 nodes as well as for 4096 nodes. Furthermore, as the number of nodes increases, the diameter and average distance of hierarchical networks improve significantly than conventional mesh and torus networks.…”
Section: Hop Distance Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of conventional networks in the evaluation was because of their current usage by supercomputers [34]. In addition, an MTN is compared to other HINs, including a midimew-connected mesh network (MMN) [35], a tori-connected mesh network (TESH) [36], a tori-connected flattened butterfly network (TFBN) [37], and a tori-connected torus network (TTN) [38].…”
Section: Introductionmentioning
confidence: 99%